2012
DOI: 10.18002/rama.v5i2.112
|View full text |Cite
|
Sign up to set email alerts
|

Detección de talentos en practicantes de taekwondo

Abstract: ResumenSe presenta una visión general de las características de deportistas jóvenes de taekwondo que parecen contribuir al rendimiento. Se resumen las conclusiones de la literatura científica, con el objeto de destacar el conocimiento actual respecto a los componentes físicos y psicológicos que se consideran importantes para tener éxito en la competición. Para aumentar las posibilidades de que los jóvenes practicantes de taekwondo se conviertan en adultos campeones, es necesaria una óptima infraestructura, ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…Theoretically, a longer lower limbs becomes a longer lever to generate more power in kicking techniques, and a longer striking distance than the opponent provides advantage in order to reach the scoring area (De la Fuente & Gómez-Landero Rodríguez, in press; Kazemi, Waalen, Morgan, & White, 2006;Markovic, Misigoj-Durakovic, & Trninic, 2005). Related to this idea, authors like Bridge et al, (2014), Kazemi et al (2013), Pieter (2010), Kazemi et al (2006) and Markovic et al (2005) have reported that more successful athletes are taller than their regular counterparts. Dubnov-Raz et al (2015) have studied the relationship between height and weight in karate athletes, dividing them into hypothetical height categories and hypothetical weight categories and calculating how many participants fit into corresponding divisions of both categorizations.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, a longer lower limbs becomes a longer lever to generate more power in kicking techniques, and a longer striking distance than the opponent provides advantage in order to reach the scoring area (De la Fuente & Gómez-Landero Rodríguez, in press; Kazemi, Waalen, Morgan, & White, 2006;Markovic, Misigoj-Durakovic, & Trninic, 2005). Related to this idea, authors like Bridge et al, (2014), Kazemi et al (2013), Pieter (2010), Kazemi et al (2006) and Markovic et al (2005) have reported that more successful athletes are taller than their regular counterparts. Dubnov-Raz et al (2015) have studied the relationship between height and weight in karate athletes, dividing them into hypothetical height categories and hypothetical weight categories and calculating how many participants fit into corresponding divisions of both categorizations.…”
Section: Introductionmentioning
confidence: 99%
“…The question we want to explore is whether children belonging to the same category of competition have different maturations, which leads to an unbalanced confrontation, since athletes with higher maturation levels have greater physical skills (Anderson & Ward, 2002;Backous et al, 1990;Pieter, 2012;Towlson et al, 2018), which in turn increases the chance of winning (Gabbett, 2015). Analyzing these evaluations by the category of competition, we found that there were several categories with maturational advanced athletes, showing that competitive equity may be at stake.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differences in maturation among children, chronological age remains the main criterion for equalizing the competition levels, but with limited efficiency (Malina, 2000). These differences in maturation among athletes or differences between chronological and biological age have been studied since the beginning of the 20 th century (e.g., Crampton, 1908), and have pointed out that maturational status had significant influences in physical fitness (Anderson & Ward, 2002;Backous, Farrow, & Friedl, 1990;Towlson, Cobley, Parkin, & Lovell, 2018), performance (Pieter, 2012), and body dimensions (Backous et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, el estudio de la composición corporal es uno de los criterios para la especialización de cualquier deporte, (Reilly, 2008, López et al, 2016, 2017) y más concretamente en vela ya que cada clase presenta una serie de exigencias, obligando a los regatistas a poseer una determinada morfología corporal (Bojsen-Moller et al, 2007) Se ha visto que el peril antropométrico de los regatistas de las diferentes clases inluye en el resultado, (Neville et al, 2009;Polato et al, 2007) así como el somatotipo puede ser un indicador relativo del rendimiento, (Matsudo, 1996, citado en Pieter, 2010) por lo que el seguimiento de la evolución de los jóvenes deportistas es una de las principales funciones asumidas por clubes y federaciones deportivas en la actualidad, creando en diferentes deportes el peril antropométrico de los atletas (Correa, 2008;López et al, 2013;Pieter, 2010;Muros et al, 2016). Este tipo de valoraciones permiten, no sólo el control de su salud y rendimiento, sino también detectar talentos deportivos para etapas posteriores de sus carreras deportivas, e incluso comparar su crecimiento con los actuales deportistas destacados de su disciplina (Pazo, 2010).…”
Section: Introductionunclassified